Inoculation with Lentilactobacillus buchneri alone or in combination with Lentilactobacillus hilgardii modifies gene expression, fermentation profile, and starch digestibility in high-moisture corn - Drouin, Pascal; da Silva, Érica Benjamim; Tremblay, Julien; Chevaux, Eric; Apper, Emmanuelle; Castex, Mathieu (Frontiers in Microbiology, 2023)
to improve the aerobic stability of high-moisture corn (HMC) and whole-plant corn silage, but the mode of action of this co-inoculation remains to be elucidated. This study used metatranscriptomics to evaluate the effects of inoculation with L. buchneri alone or combined with L. hilgardii on the bacterial community, gene expression, fermentation profile, and starch digestibility in HMC. Highmoisture corn not inoculated (Control) or inoculated with L. buchneri NCIMB 40788 (LB) or L. buchneri NCIMB 40788 combined with L. hilgardii CNCM-I-4785 (Combo) was ensiled in mini silo bags for 30, 60, 120, and 180 days. The fermentation profile was evaluated at all time points. Metatranscriptomics was performed on samples collected on day 120. Combo had a greater alpha Inoculated HMC gene expression 2 diversity richness index of contigs than LB and Control, and inoculation with Combo and LB modified the beta-diversity of contigs compared to Control. Out of 69 genes of interest, 20 were differentially expressed in LB compared to Control and 25 in Combo compared to Control. Of those differently expressed genes, 16 (10 of which were associated with carbohydrate metabolism and six with amino acid metabolism) were differently expressed in both LB and Combo compared to Control, and all those genes were upregulated in the inoculated silages. When we compared Combo and LB, we found seven genes expressed differently, four associated with carbohydrate metabolism and downregulated in Combo, and three associated with amino acid metabolism and upregulated in Combo. At day 120, the inoculated silages had more culturable lactic acid bacteria, higher Lactobacillus relative abundance, and lower Leuconostoc relative abundance than Control. The concentration of acetic acid remained low throughout ensiling in Control, but in LB and Combo, it increased up to day 60 and remained stable from day 60 to 180. The 1,2-propanediol was only detected in LB and Combo. Inoculation did not affect the concentration of starch, but starch digestibility was greater in Combo than in Control. Inoculation of HMC with Combo modified the gene expression and fermentation profile compared to Control and LB, improving starch digestibility compared to uninoculated HMC.